The Boma: Animal-source foods for people and the planet - International Livestock Research Institute (International Livestock Research Institute, 2021)
As the pandemic pushes global malnutrition to rates not seen in more than a decade, how can livestock products like milk, meat and eggs help? And how do we weigh the nutritional benefits of livestock, particularly in the developing world, against the fact that livestock can be a significant source of greenhouse gas emissions? In this episode of The Boma, presenters Brenda Coromina and Elliot Carleton talk to Lora Iannotti, a specialist in child and maternal nutrition, as they explore why context and food choices matter when it comes to avoiding malnutrition. Award-winning holistic farmer Emma Naluyima explains how integrated farming techniques can reduce the carbon footprint of livestock farming, and gives her vision for how children can become responsible global citizens of the future. Finally, Susan MacMillan, Emeritus Fellow at ILRI, describes her dream future for livestock in a more equitable and sustainable world.